2015
DOI: 10.1177/2055102914566290
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of how parents assess acute pain in young children

Abstract: An accurate and comprehensive pain assessment is crucial for adequate pain management in pre- and early verbal children during painful medical procedures. This study used an inductive approach to explore the processes involved in parental pain assessment and to develop a new model of Parental Assessment of Acute Child Pain. Participants were 19 parents of children aged under 3 years who had previously or were potentially about to experience an intravenous cannula or nasogastric tube insertion. Parental affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…This tool has been assessed against a number of criteria in earlier studies of children during their early and later (i.e., in patient) surgical recovery phases (48-50). While some studies have shown variances, others have found that the parent and child's reported pain levels coincide (51)(52)(53). In the present study, there was no difference between parents' and their children's ratings.…”
Section: Discussioncontrasting
confidence: 62%
“…This tool has been assessed against a number of criteria in earlier studies of children during their early and later (i.e., in patient) surgical recovery phases (48-50). While some studies have shown variances, others have found that the parent and child's reported pain levels coincide (51)(52)(53). In the present study, there was no difference between parents' and their children's ratings.…”
Section: Discussioncontrasting
confidence: 62%
“…Anxiety and dispositional empathy were not predictors of participants’ judgment accuracy in the current study, and parental pain catastrophizing only accounted for a small amount of variance in underestimation of girls’ pain. Future research could explore these variables in a clinical context, as well as other variables that might predict caregivers’ estimations of children’s pain and fear, such as parents’ emotion regulation abilities 31 or their own responses to pain (e.g., parent pain tolerance, their own pain catastrophizing 16 ). Further, trait measures of anxiety, parental pain catastrophizing, and empathy were examined in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the inclusion of parents' observations and judgments may offer an enhanced pain assessment compared with that centered on the patient's experience and clinician's observation [ 30 ]. Some studies have reported that the parent and child reported pain ratings match, whereas other studies have reported differences [ 31 33 ]. In our study, there was no difference between the two groups in parents' ratings of child's tolerance of injection.…”
Section: Discussionmentioning
confidence: 99%